(untitled) (Third Sector Social Economic Review, 2023)
Communication technologies have brought along specific problems as well as the conveniences to our lives. Especially with the spread of social media usage, physical bullying has been taken to the virtual environment via social media which is referred as cyberbullying. The present study seeks to reveal social media platforms where women are subjected to cyberbullying, reasons, experiences and emotional effects of bullying, use of social media after bullying and solutions to prevent cyberbullying. In this context, a qualitative method in line with the purpose of the study is adopted.Within this study, profound individual interviews with 20 women selected via snowball sampling method. In addition, a semi-structured interview protocol was used as a data collection tool. All interviews were conducted face-to-face. According to the results of this study, women within the sample group were subjected to cyberbullying on Instagram, Twitter, LinkedIn and Facebook. Types of cyberbullying the women were subjected to hacking into social media passwords, sending abusive messages, spreading personal photos, videos and information and stalking. The most common reactions of the participants who were subjected to cyberbullying were irritability, anxiety, sadness and fear. With regards to the participants’ use of social media after cyberbullying, it is noted that they had either made their social media accounts private or closed them, had not shared anything for a long time and had deleted their photos on their accounts. Moreover, among the reasons for being subjected to cyberbullying, participants expressed the role of personal problems of the bully, bully being an ex-boyfriend, bully’s lack of confidence and unhappiness. As a conclusion to this study, this paper recommends that further studies should be done in order to increase the awareness of women about cyberbullying.